Strategic Leadership in Islamic Education: Enhancing School Effectiveness through Faith-Based Management Approaches - Ubaydillah Al-asror; Muhammad Irsyad Baitussalam (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
This study explores the role of strategic leadership in Islamic education as a driver of school effectiveness through faith-based management approaches. Islamic education carries a dual mission: achieving academic excellence while fostering moral and spiritual values. Thus, leadership requires not only managerial competence but also the integration of Islamic principles such as amanah (trust), adl (justice), and ihsan (excellence). Adopting a qualitative library research approach, this paper reviews theoretical perspectives and prior studies on educational leadership to analyze how strategic leadership aligns institutional goals with both contemporary demands and Islamic values. The findings indicate that faith-based strategic leadership strengthens school culture, enhances teacher performance, and supports student achievement by combining modern management practices with religious ethics. The study concludes that strategic leadership rooted in Islamic principles enriches educational management by embedding ethical and spiritual dimensions into leadership practices. This integration enables Islamic schools to remain academically competitive while preserving their religious mission, providing valuable insights for leaders and policymakers committed to advancing effective and value-driven education.